Mitochondrial ATP6 and ND3 genes are associated with type 2 diabetic peripheral neuropathy. Issue 6 (June 2022) - Kasinathan, Devi; Matrougui, Khalid; Elango, Santhini; Belmandani, Souad; Srinivas, Balaji; Muthusamy, Karthikeyan; Narayanasamy Marimuthu, Prabhu
Abstract: Background and aims: The association of mitochondrial NADH dehydrogenase gene mutations with type 2 diabetes in the Karaikudi population was previously reported. This is a case report that demonstrated rare mutations are responsible for maternally inherited peripheral neuropathy of diabetes. Methods: We describe a 70-year-old male and his family (n = 25) with type 2 diabetic peripheral neuropathy having four rare mutations, 8597T > C, 8699T > C, 8966T > C, 10188A > G, and 9 bp deletion in various regions of the mitochondrial genes. Mutations were identified through direct sequencing of DNA isolated from the blood of the selected individuals. Blood samples were also analyzed for glucose, hemoglobin A1c, triglyceride, total cholesterol, oxidative stress markers, antioxidant status, cytochrome-C-oxidase and mitochondrial DNA content using appropriate methods. Results: Oxidative stress markers were found elevated while the antioxidant status, mitochondrial DNA content and the activity of cytochrome C-oxidase was reduced significantly. Analysis of mtDNA showed the presence of several mutations in various regions of mitochondrial genome. However, 8597T > C, 8699T > C, 8966T > C, 10188A > G, and 9 bp deletion were observed in the patient's family including his siblings. Conclusion: This study shows that the mutations observed in the patient and his family is maternally inherited and suspected to be pathogenic in developing T2D associated peripheral neuropathy.